The bullet [large type] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller, 2021)
"After being divorced from Joe Quinn for many years, Diane Connors abruptly returns to disrupt his life by begging his current wife, Eve Duncan, to do her a favor. Diane is on the run with a secret that will not only put Eve in danger but make her choose between protecting her family and doing what is right. Diane is not Eve's favorite person. But years of animosity must be cast aside because Diane is no longer the selfish woman that Eve once knew. She has become a selfless doctor who has discovered a silver bullet that will change life for everyone on the planet. And she's fighting evil forces to ensure that her miracle cure is made public. But to do that, she has to remain alive, and Eve must be by her side in the battle. Even when the memories of Diane and Joe together are a personal challenge that Eve must face"--